Memahami alur informasi penemuan, evaluasi, dan pemrosesan menuju pengetahuan: Studi literatur - Anggrainie, Agustina (Maliki Interdisciplinary Journal, 2025)
In today’s digital era, access to information is very easy and fast; however, not all available information possesses adequate quality and credibility. Therefore, an individual’s ability to find, evaluate, and process information is crucial in order to acquire valid and relevant knowledge. This article discusses three main stages of information literacy: information discovery, information evaluation, and information processing. Information discovery begins with an individual’s need that drives the search for relevant sources. Information evaluation is necessary to assess the validity and credibility of information to avoid falling prey to hoaxes or biased content. Meanwhile, information processing involves organizing and storing data into knowledge that can be applied in academic as well as professional contexts. Mastery of these skills forms the fundamental basis for facing the challenges of today’s information flow and optimally utilizing technological opportunities.